Evaluation, treatment, complications, and prognosis of craniosynostosis - Sindy, Ebtihal A.; Aloudah, Ebtehal M.; Alamani, Saud F.; Alqahtani, Abdullah M.; Alawad, Hussain R.; Alteraigi, Abdullah A.; Alrawsaa, Faisal A.; Alharbi, Mohammed S.; Sangoura, Suzan I.; Shehatah, Ahmad U.; Hakami, Reem M. (International Journal Of Community Medicine And Public Health, 2023)
Craniosynostosis is a congenital craniofacial anomaly that typically presents at birth and affects the skull’s shape. It is characterized by the premature fusion of one or more cranial sutures in infants, which can impair brain development and function. While craniosynostosis is considered rare, it has a global prevalence of around three to six cases in 10,000 live births. This review article aims to synthesize the latest developments in diagnostic techniques, treatment strategies, and potential complications for the benefit of healthcare providers, researchers, and affected families. This review commenced on 31 October 2023, following a thorough examination of existing literature. Diverse databases, including PubMed, Web of Science, and Cochrane, were utilized for the literature review. Early diagnosis and evaluation involve a multidisciplinary approach, including clinical assessments, medical history reviews, and advanced imaging techniques like computed tomography (CT) scans and magnetic resonance imaging (MRI). Surgical intervention is the primary treatment option, with the goal of releasing or reshaping the fused sutures to allow for normal skull growth. While open surgical procedures like suturectomy have been prevalent, less invasive methods like minimally invasive endoscopic strip craniectomy are becoming more popular due to reduced complications. Untreated craniosynostosis can lead to complications such as increased intracranial pressure, developmental delays, vision and hearing problems, and psychosocial impacts, emphasizing the importance of timely intervention. However, surgical treatments carry their own risks, necessitating a well-planned and individualized approach. Overall, the prognosis for craniosynostosis is generally positive, and factors such as the specific type of craniosynostosis, the timing of treatment, and the quality of post-operative care all influence outcomes. Prenatal diagnosis and multidisciplinary care have emerged as valuable tools for improving prognosis.